Implementing Regtech for Fintech Startup: A Solution to Overregulation in Developing Countries - Vivek Sharma (Start-up and Financial Technology, 2026)
Objective: This study aims to comprehensively analyze how the implementation of Regulatory Technology (RegTech) can be a strategic solution in overcoming the challenges of overregulation faced by FinTech startups in developing countries, which often hinder innovation and financial inclusion. Research Design & Methods: This study adopts a qualitative approach, with the primary method being an extensive literature review of scientific journal articles, industry reports, and other relevant publications. Furthermore, it utilizes comparative case studies from various developing countries. Findings: The research findings show that overregulation of FinTech startups in developing countries manifests itself in rigid licensing regimes, high capital requirements, overlapping oversight, high compliance costs, and data privacy and cybersecurity issues. RegTech, with its compliance automation, predictive risk management, streamlined regulatory reporting, and enhanced KYC/AML capabilities powered by AI, ML, big data, cloud computing, and blockchain, has been shown to significantly improve operational efficiency, reduce compliance costs, increase accuracy, and offer scalability and adaptability to regulatory changes. Case studies confirm RegTech's positive impact in combating financial crime and driving innovation. Implications: This research confirms that RegTech plays a strategic role in driving FinTech growth, with policy implications including adaptive regulations, cross-sector collaboration, harmonization of standards, and investment in infrastructure and human resource development.Contribution & Value Added: This research presents an in-depth analysis of the role of RegTech in addressing overregulation in developing countries, and offers practical policy recommendations to support a healthy and inclusive FinTech ecosystem.